Analisis Penjualan Listrik dalam Meningkatkan Perolehan Laba Pada PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan Bontang - Mustari Mustari; Muhammad Siddiq; Anis Aulia Muslim; Delianti Delianti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
The implementation of prepaid electricity enables households to monitor and control their electricity consumption. The system functions similarly to mobile phone credit top-ups. One key advantage of prepaid electricity is the elimination of late payment penalties. Compared to postpaid electricity, the prepaid system is perceived as more economical, as it encourages consumers to be more prudent and efficient in their energy usage.Prepaid electricity services operate on a pay-before-use basis, offering flexibility and better cost management to consumers. This study aims to analyze the impact of electricity sales on profit growth at PT PLN (Persero) UP3 Bontang. The research adopts a quantitative approach using descriptive statistical analysis based on financial data from the last five years (2016–2020). The findings reveal that, although there has been an increase in both the volume and value of electricity sales, this does not necessarily translate into increased company profits. The stagnation or decline in profit is primarily attributed to high operational costs, including power plant fuel expenses, electricity purchases from independent power producers (IPPs), network maintenance costs, and exchange rate fluctuations.